2022
DOI: 10.1371/journal.pcbi.1010419
|View full text |Cite
|
Sign up to set email alerts
|

Robust inference of population size histories from genomic sequencing data

Abstract: Unraveling the complex demographic histories of natural populations is a central problem in population genetics. Understanding past demographic events is of general anthropological interest, but is also an important step in establishing accurate null models when identifying adaptive or disease-associated genetic variation. An important class of tools for inferring past population size changes from genomic sequence data are Coalescent Hidden Markov Models (CHMMs). These models make efficient use of the linkage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Our results suggest that population-size decline could be linked to the transition to selfing and that our demographic inference using teSMC should be more reliable than those from eSMC (and other SMC approach ignoring the selfing transition). A way forward would be to improve our inference framework using the new theoretical results by Upadhya and Steinrücken, 2022 , which focuses on modeling the time to the most recent common ancestor of a sample size bigger than two. This study demonstrates that the inference in the far past can be improved, at the cost of losing accuracy in recent times.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that population-size decline could be linked to the transition to selfing and that our demographic inference using teSMC should be more reliable than those from eSMC (and other SMC approach ignoring the selfing transition). A way forward would be to improve our inference framework using the new theoretical results by Upadhya and Steinrücken, 2022 , which focuses on modeling the time to the most recent common ancestor of a sample size bigger than two. This study demonstrates that the inference in the far past can be improved, at the cost of losing accuracy in recent times.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, extreme rates of recombination (cM/Mb ≤ 0.01, cM/Mb ≥ 5) have been shown to result in mis-inference of historical population size as calculated from nucleotide diversity using Relate (Novo et al 2022). However, Upadhya and Steinrücken (2022) suggested that demographic inference performance with Relate improves when recombination rates are variable due to the presence of low recombination rate regions from which exact local genealogies can be estimated, which could in part explain the moderate improvement provided by modelling mutation and recombination rate heterogeneity in D. melanogaster simulated populations (Figure S3). It is unclear whether recombination and mutation rate heterogeneity may have more substantial effects in different species, as recent reports suggest masking low-recombination regions in songbird species may improve demographic inference with Relate (Ishigohoka and Liedvogel 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic ARG estimation using exhaustive likelihood approaches is computationally impractical (McVean and Cardin 2005), and as a result, Relate and similar methods use heuristics and HMMs to minimise redundant calculations (Li and Stephens 2003), greatly improving scalability with large sample sizes at the cost of precision. Relate (Speidel et al 2019) and tsinfer/tsdate (Kelleher et al 2019; Wohns et al 2022) share biases when estimating recent and ancient coalescence times (Brandt et al 2022; Upadhya and Steinrücken 2022), where accuracy drops when compared to e.g . the less scalable, more precise ARGweaver (Rasmussen et al 2014), likely due to factors such as under-sampling of marginal trees (Deng et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With the rise of SMC approaches [53], most current methods leverage information from whole genome sequences by simultaneously reconstructing a portion of the ARG in order to infer past demographic history [53, 77, 88, 89], migration rates [46, 90], variation in recombination and mutation along the genome [5, 4], as well as ecological life history traits such as selfing or seed banking [80, 86]. However in previous studies authors discussed uncoupling both steps, namely reconstructing the ARG and then inferring parameters from its distribution [81, 31, 68].…”
Section: Discussionmentioning
confidence: 99%